Adaptive noise clipping-based hybrid progressive median filter for image transmission over top-down powerline communication. (2016) - Himeur, Yassine; Boukabou, Abdelkrim
In this paper, we propose a dual noise reduction technique to robustly carry on images through powerline communication (PLC) network. An adaptive noise clipping-based hybrid progressive median filter (ANC-HPMF), which is a combination of a new median filter, noise clipping technique and OFDM modulation, is designed to ensure robust image transmission over the PLC channel. Firstly, the ANC technique to clip the impulsive noise in the physical layer using neighbouring coefficients is designed. It is based on an improved estimation of noise threshold from the standard deviation of the noise and the peak value of the received noisy signal. Secondly, to enhance the performance of ANC, we proposed a new filter namely HPMF to be applied to the received image on the application layer as a second stage for impulsive noise reduction. A high capability for impulsive noise suppression is reached while maintaining good visual quality by preserving the edges.